AID hits the jackpot when missing the target. (April 2016) - Kenter, Amy L; Kumar, Satyendra; Wuerffel, Robert; Grigera, Fernando
Highlights: AID is guided by non-coding germline transcipts to switch region targets. Integration of transcription and AID targeting with class switch recombination. AID deamination function intersects with global DNA demethylation. AID regulation of genomic DNA methylation may regulate gene expression. Abstract : Activation induced deaminase is the single B cell specific factor mediating class switch recombination and somatic hypermutation. Numerous studies have shown that AID preferentially targets Ig substrates and also attacks non-Ig substrates to create DNA damage that contributes to lymphomagenesis. AID targeting to Ig loci is linked to transcription but the mechanism governing this process has been obscure. Here we discuss research that illustrates the connection between AID targeting to DNA substrates and transcription processes to reveal rules governing the specificity of AID attack. These observations are woven together to provide a integrated view of AID function and a surprising linkage with global regulation of gene expression.